Correlation Analysis of Quality, Ability and Performance of Information Technology Usage on Registration Section of RSI Siti Rahmah Padang, Indonesia - Yanti Desnita Tasri (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
Patient care in the registration section of the hospital is a very important activity, because there is a recording of patient data that will be used by other health workers in providing further health care. The use of information technology in the registration section can increase work effectiveness and efficiency and produce accurate information. For this reason, it is necessary to analyze the factors that affect the benefits of using information technology in the registration section. This study aims to examine the relationship between the quality of information systems, the ability of officers and the performance of information users at RSI Siti Rahmah Padang, Indonesia. The research was conducted with survey method and data analysis using a quantitative approach. From the research results, it was found that the quality of information systems did not affect the benefits of using information technology. Meanwhile, the ability and performance of officers affect the benefits of using information technology. It is suggested that the scope of the use of information technology in the medical records section be increased. It is necessary to increase the ability of officers in the use of information technology by holding training or workshops.